Identification of c-FLIPL and c-FLIPS as critical regulators of death receptor-induced apoptosis in pancreatic cancer cells. Issue 2 (28th September 2010) - Haag, Christian; Stadel, Dominic; Zhou, Shaoxia; Bachem, Max G; Möller, Peter; Debatin, Klaus-Michael; Fulda, Simone
Abstract : Background: Evasion of apoptosis is a hallmark of pancreatic cancer. However, the underlying mechanisms are still only partly understood and may involve antiapoptotic proteins such as c-FLIP. Here, the role of c-FLIP in the regulation of death receptor-mediated apoptosis in pancreatic cancer was investigated. Methods: Expression of c-FLIPL and c-FLIPS was analysed in primary pancreatic carcinoma samples, pancreatic carcinoma cell lines and primary tumour cells together with its function as a regulator of death receptor-induced apoptosis by knockdown and overexpression studies and through modulation by chemotherapeutics. Results: c-FLIP is expressed in pancreatic intraepithelial neoplasm (PanIN) lesions and in pancreatic ductal adenocarcinomas, whereas normal pancreatic ducts were consistently negative for c-FLIP. Simultaneous downregulation of c-FLIPL and c-FLIPS as well as individual knockdown of either isoform by RNA interference significantly enhances TRAIL (tumour necrosis factor-related apoptosis-inducing ligand)- and CD95-induced caspase activation and caspase-dependent apoptosis. Also, pretreatment with chemotherapeutic drugs—that is, 5-fluorouracil (5-FU), cisplatin or gemcitabine—downregulates c-FLIP and renders cells sensitive to death receptor-triggered apoptosis. Similarly, primary cultured pancreatic cancer cells are primed for TRAIL-induced apoptosis by pre-exposure to 5-FU or cisplatin. Mechanistic studies revealed that 5-FU-mediated suppression of c-FLIP results in increased TRAIL-induced recruitment and activation of caspase-8 at the death-inducing signalling complex (DISC), leading to caspase-3 activation and caspase-dependent cell death. Overexpression of c-FLIPL rescues cells from 5-FU- or cisplatin-mediated sensitisation for TRAIL-induced apoptosis, indicating that c-FLIP suppression is a key event in this chemotherapy-mediated sensitisation to TRAIL. Further, concomitant neutralisation of c-FLIP and XIAP acts in concert to potentiate TRAIL-induced apoptosis. Conclusions: Both the long and the short isoform of the antiapoptotic protein c-FLIP are critical regulators of death receptor-induced apoptosis in pancreatic carcinoma cells and are suppressed by chemotherapeutics. Targeting either c-FLIPL or c-FLIPS is sufficient to promote death receptor-induced apoptosis in pancreatic carcinoma cells. These findings have important implications for the design of TRAIL-based combination protocols in pancreatic cancer.